Phagocytic activity of peripheral blood and crevicular phagocytes in health and periodontal disease - Asif K; Kothiwale Shaila (Wolters Kluwer Medknow Publications, 2010)
Background: Neutrophils constitute the main phagocytic cell system in mammalian host defense against an infecting agent. Abnormalities in leukocyte number and function are associated with increased susceptibility to periodontal diseases. The purpose of this study is to evaluate the in vitro phagocytic properties of crevicular and peripheral blood neutrophils in healthy and periodontitis subjects. Patients and Methods: A total of 30 subjects, that is, 10 patients in each of the following three groups: healthy controls, chronic periodontitis (CP), and localized aggressive periodontitis (LAP), were included in the study. The neutrophils were isolated from the peripheral blood and gingival crevice and tested for phagocytosis of Candida albicans. The percentage of leukocytes with ingested C. albicans was determined by light microscopy. Results: A significant reduction in the phagocytic activity of crevicular fluid polymorphonuclear neutrophils (CF-PMN) of LAP subjects (mean: 54.3±7)(P< 0.001) was observed, compared to healthy controls (mean: 74.2±9) and chronic periodontitis subjects (mean: 69±9)(P=0.352). The mean percentage of peripheral blood polymorphonuclear neutrophils (PMNs) with phagocytosis of opsonized C. albicans in LAP patients was significantly reduced (mean: 74.9±5)(P< 0.0068) compared to the phagocytic activity of neutrophils from controls (mean:82.1±3) and chronic periodontitis subjects (mean: 82.0±5)(P=0.970). There was no significant reduction in the phagocytic activity of CF PMNs (mean: 69±9) (P=0.35) and peripheral blood PMNs (mean: 82.5)(P=0.97) in the chronic periodontitis group when compared to the control group. Conclusion: The phagocytic activity of both crevicular and peripheral neutrophils in subjects with periodontitis is altered, increasing the susceptibility to periodontitis. Thus individual susceptibility may be an additional and important modifying factor in the pathogenesis of periodontal disease.